Pesticide residues in food and drinking water : (John Wiley & Sons, Ltd, 2004)
This book explores human exposure and consumer risk assessment in response to issues surrounding pesticide residues in food and drinking water. All the three main areas of consumer risk assessment including human toxicology, pesticide residue chemistry and dietary consumption are brought together and discussed.